EVALUASI IMPLEMENTASI PELAYANAN FARMASI KLINIS DI PUSKESMAS : STUDI KASUS DI KECAMATAN BANJARMASIN UTARA - Hendera, Hendera; Mulyani, Risya; Iftikhar, Ahmad Akmal (Jurnal Insan Farmasi Indonesia, 2024)
Clinical pharmacy services in primary healthcare centers (Puskesmas) are crucial components of the primary healthcare system. However, their implementation remains varied and suboptimal across different regions in Indonesia. This study aimed to evaluate the implementation of clinical pharmacy services in Puskesmas within North Banjarmasin District based on established quality indicators. This cross-sectional observational study was conducted in five Puskesmas in North Banjarmasin District. The evaluation used 19 clinical pharmacy service quality indicators developed through a modified Delphi method. Data were analyzed descriptively, the Friedman test was used to compare service quality. Clinical pharmacy service achievements varied among Puskesmas, 36% to 63%. Puskesmas A showed the best performance (63%, good category), while Puskesmas D was the lowest (36%, poor category). Aspects showing good performance included prescription service time and generic drug use. Areas needing improvement included prescription review documentation, drug labeling, and implementation of advanced clinical pharmacy services. The Friedman test showed no significant difference in service quality among Puskesmas (p > 0.05). The implementation of clinical pharmacy services in North Banjarmasin District Puskesmas varies and requires improvement. A coordinated strategy for standardizing procedures, capacity building, and strengthening documentation systems is needed to optimize clinical pharmacy services at the Puskesmas level.